Solvation Behaviour of Some Copper(I) Nitrate Complexes in Dimethylsulfoxide and Nitromethane at 298 K - Pathania, Vivek; Kaur, Manpreet; Vermani, B.K.; Sharma, Shrutila; Grover, Navya (Asian Journal of Chemistry, 2021)
The ultrasonic velocities of solutions of Bu4NBPh4, Bu4NClO4, [Cu(AN)4]NO3, [Cu(BN)4]NO3, [Cu(Phen)2]NO3, [Cu(DMPhen)2]NO3, [Cu(Bipy)2]NO3 and [Cu(TU)4]NO3 (where AN = acetonitrile, BN = benzonitrile, Phen = 1,10-phenanthroline, DMPhen = 2,9-dimethyl-1,10-phenanthroline, Bipy = 2,2′-bipyridyl and TU = thiourea) were measured in the concentration range 0.03-0.27 M in dimethylsulfoxide (DMSO), nitromethane (NM) and binary mixtures of DMSO + NM containing 0, 20, 40, 60, 80 and 100 mol% NM at 298 K in the present studies. Using ultrasonic velocity and density data, isentropic compressibility (κs) and apparent molal isentropic compressibility (κs,f) for electrolytes in DMSO + NM mixture have been calculated. Result shows that copper(I) electrolytes show less solvation in NM rich regions indicating structure breaking tendency of nitromethane. Extent of solvation in Cu(I) ions decreases in the order: [Cu(AN)4]+ > [Cu(BN)4]+ > [Cu(TU)4]+ > [Cu(DMPhen)2]+ > [Cu(Phen)2]+ > [Cu(Bipy)2]+.